AB0145 Impaired healing of anterior cruciate ligament correlates with kinins expression. (23rd January 2014) - Savitskaya, Y.; Tellez, R.; Martinez, E.; Cruz, F.; Almazan, A.; Ibarra, C.
Abstract : Background: ACL is the most frequently injured ligament of the knee, with over 100, 000 reconstructions performed annually. Reconstruction of injured ligaments is still a problem. The discovery that cartilage can make products of the kinin-kallikrein pathway and its receptors suggests that it can not only respond to products of the pathway but initiate this inflammatory process in the joint by providing bradykinin (BK). An understanding of the process of ACL healing evolves, new markers will be indentified that will be accurate measures of this process. Objectives: The purpose of the study was to define the levels of serum markers C1, 2C, C2C (cartilage degradation), CPII, CS846 (cartilage formation), natural (IgA, IgM, IgG) antibodies against BK (healing of ACL) in a cohort of patients before and after ACL reconstruction and compare them to matched, uninjured controls. Methods: Patients undergoing ACL reconstruction were matched with uninjured controls of similar age, sex, and BMI. Serum drawn upon entry to USMA and prior to graduation from both groups were tested ELISA kits (IBEX, Inc, Montreal, CA). In order to quantify NA to BK in the sera, were designed, synthesized and then used to develop a novel ELISA kits (INR). Results: There was no significant difference in binding of serum BK-IgA and BK-IgG levels in ACL patients in comparison with that in controls. Serum BK-IgM levels is elevated in patients after ACL reconstruction and correlate with individual and composite measures of the healing activity.There were significant differences (p<0.05) in the C2C and CPII levels between groups pre-injury, but not the C1, 2C and CS846 levels. There were significant differences (p<0.05) in the C1, 2C, C2C, and CPII levels between groups in the post-reconstruction state, but not for CS846. Comparing within group changes, all markers were significantly different over time (p<0.05) in both groups except for the controls C1, 2C and ACL injured CS846. Significant group by time interactions were observed (p<0.05) for C2C and CS846. Elevated BK-IgM in the sera was significantly correlated with C2C (r=0.85; p<0.0001) and CII (r=0.69; p<0.0003) in ACL patients in the post-reconstruction state. Conclusions: The process of ACL healing is highly complex, but is slowly starting to become more well defined. A significant relationship was found between the examined markers of cartilage formation and degradation and the dynamic change of serum levels of kinins after ACL reconstruction. The difference in BK-IgM, CPII and C2C levels in the pre-injury state suggests that there may be differences in cartilage metabolism of individuals at risk for ACL tear. Significant changes over time were observed in kinins markers in the ACL-injured group and further study is warranted into the prognostic capabilities of these markers. References: Couture R: Kinin receptors in pain and inflammation. Eur J Pharmacology 2001, 429(1-2):161-176. Disclosure of Interest: Y. Savitskaya Grant/Research support from: FONSEC SSA/IMSS/ISSSTE/CONACyT SALUD-2010-C01, R. Tellez: None Declared, E. Martinez: None Declared, F. Cruz: None Declared, A. Almazan: None Declared, C. Ibarra: None Declared